1995
DOI: 10.1084/jem.181.2.747
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial superantigens induce T cell expression of the skin-selective homing receptor, the cutaneous lymphocyte-associated antigen, via stimulation of interleukin 12 production.

Abstract: SummaryT lymphocyte infiltration is a prominent feature of the skin inflammation associated with infections by toxin (superantigen)-secreting Staphylococcus aureus or Streptococcus bacteria. The cutaneous lymphocyte-associated antigen (CLA) has been hypothesized to be a homing receptor (HR.) involved in selective migration of memory/effector T cells to the skin. Since the expression of this putative skin-selective HR is known to be under strict microenvironmental control, we sought to determine the effect of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
186
1
5

Year Published

1996
1996
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(199 citation statements)
references
References 39 publications
7
186
1
5
Order By: Relevance
“…APC). In addition, we tested IL-12 as a single cytokine whereas Leung et al 34 tested the effect of IL-12 in the presence of IL-2, which might give potentiating effects.…”
Section: Discussionmentioning
confidence: 99%
“…APC). In addition, we tested IL-12 as a single cytokine whereas Leung et al 34 tested the effect of IL-12 in the presence of IL-2, which might give potentiating effects.…”
Section: Discussionmentioning
confidence: 99%
“…Superantigens have recently been shown to induce a selective expression of the skin homing receptor cutaneous-lymphocyte associated antigen, CLA [67]. Furthermore, superantigen activated mononuclear cells have been reported to induce psoriatic change in skin grafts on SCID mice [8].…”
Section: Psoriatic T Cells Respond To M-peptides Sharing Sequences Wimentioning
confidence: 99%
“…Yudate et al [19] showed that PBMCs from children with AD, demonstrated enhanced proliferation of SEB. Leung et al [20] also proposed that the Staphylococcal superantigens, secreted at the skin surface, might penetrate through the inflamed skin and stimulate Langerhans' cells to produce IL-12, upregulating the expression of CLA on T cells. Trautmann et al [21] suggested that, in peripheral blood of AD patients, both CD4 and CD8 subsets of CLA CD45RO T cells expressed upregulated Fas and FasL and underwent apoptosis.…”
Section: Discussionmentioning
confidence: 99%